Elevated lipid oxidation is associated with exceeding gestational weight gain recommendations and increased neonatal anthropometrics: a cross-sectional analysis - Jill M. Maples; Samantha F. Ehrlich; Nikki B. Zite; Kevin J. Pearson; W. Todd Cade; Courtney J. Riedinger; Maire M. Blankenship; Rachel A. Tinius (BMC, 2021)
Abstract Background Deviations from gestational weight gain (GWG) recommendations are associated with unfavorable maternal and neonatal outcomes. There is a need to understand how maternal substrate metabolism, independent of weight status, may contribute to GWG and neonatal outcomes. The purpose of this study was to explore the potential link between maternal lipid oxidation rate, GWG, and neonatal anthropometric outcomes. Methods Women (N = 32) with a lean pre-pregnancy BMI were recruited during late pregnancy and substrate metabolism was assessed using indirect calorimetry, before and after consumption of a high-fat meal. GWG was categorized as follows: inadequate, adequate, or excess. Shortly after delivery (within 48 h), neonatal anthropometrics were obtained. Results Using ANOVA, we found that fasting maternal lipid oxidation rate (grams/minute) was higher (p = 0.003) among women with excess GWG (0.1019 ± 0.0416) compared to women without excess GWG (inadequate = 0.0586 ± 0.0273, adequate = 0.0569 ± 0.0238). Findings were similar when lipid oxidation was assessed post-meal and also when expressed relative to kilograms of fat free mass. Absolute GWG was positively correlated to absolute lipid oxidation expressed in grams/minute at baseline (r = 0.507, p = 0.003), 2 h post-meal (r = 0.531, p = 0.002), and 4 h post-meal (r = 0.546, p = 0.001). Fasting and post-meal lipid oxidation (grams/minute) were positively correlated to neonatal birthweight (fasting r = 0.426, p = 0.015; 2-hour r = 0.393, p = 0.026; 4-hour r = 0.540, p = 0.001) and also to neonatal absolute fat mass (fasting r = 0.493, p = 0.004; 2-hour r = 0.450, p = 0.010; 4-hour r = 0.552, p = 0.001). Conclusions A better understanding of the metabolic profile of women during pregnancy may be critical in truly understanding a woman's risk of GWG outside the recommendations. GWG counseling during prenatal care may need to be tailored to women based not just on their weight status, but other metabolic characteristics.